When herbivores eat predators: predatory insects effectively avoid incidental ingestion by mammalian herbivores. - Matan Ben-Ari; Moshe Inbar (PLoS ONE, 2013)
The direct trophic links between mammalian herbivores and plant-dwelling insects have been practically ignored. Insects are ubiquitous on plants consumed by mammalian herbivores and are thus likely to face the danger of being incidentally ingested by a grazing mammal. A few studies have shown that some herbivorous hemipterans are able to avoid this peril by dropping to the ground upon detecting the heat and humidity on the mammal's breath. We hypothesized that if this risk affects the entire plant-dwelling insect community, other insects that share this habitat are expected to develop similar escape mechanisms. We assessed the ability of three species (adults and larvae) of coccinellid beetles, important aphid predators, to avoid incidental ingestion. Both larvae and adults were able to avoid incidental ingestion effectively by goats by dropping to the ground, demonstrating the importance of this behavior in grazed habitats. Remarkably, all adult beetles escaped by dropping off the plant and none used their functional wings to fly away. In controlled laboratory experiments, we found that human breath caused 60-80% of the beetles to drop. The most important component of mammalian herbivore breath in inducing adult beetles and larvae to drop was the combination of heat and humidity. The fact that the mechanism of dropping in response to mammalian breath developed in distinct insect orders and disparate life stages accentuates the importance of the direct influence of mammalian herbivores on plant-dwelling insects. This direct interaction should be given its due place when discussing trophic interactions.